2001
DOI: 10.1096/fj.01-0651fje
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils as a key cellular target for angiostatin: implications for regulation of angiogenesis and inflammation

Abstract: Angiostatin effectively blocks tumor angiogenesis through still poorly understood mechanisms. Given the close association between immune and vascular regulation, we investigated the effects of angiostatin on angiogenesis-associated leukocytes. Angiostatin inhibited the migration of monocytes and, even more markedly, neutrophils. Angiostatin blocked chemotaxis of neutrophils to CXCR2 chemokine receptor agonists (IL-8, MIP-2, and GROalpha), formyl-Met-Leu-Phe (fMLP), and 12-O-tetradecanoylphorbol 13-acetate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
114
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(121 citation statements)
references
References 43 publications
7
114
0
Order By: Relevance
“…1), as previously described (10). The intensity of the angiogenic response to CXCL1/MIP-2, as estimated by the hemoglobin content, was comparable to that induced by VTH, a mixture containing TNF-␣, which increases the expression of VEGFR2 on endothelial cells (27), and VEGF-A, a potent angiogenic factor acting directly on endothelial cells (Fig.…”
Section: Evaluation Of the Angiogenic Response Induced By Cxcl1/mip-2supporting
confidence: 66%
See 2 more Smart Citations
“…1), as previously described (10). The intensity of the angiogenic response to CXCL1/MIP-2, as estimated by the hemoglobin content, was comparable to that induced by VTH, a mixture containing TNF-␣, which increases the expression of VEGFR2 on endothelial cells (27), and VEGF-A, a potent angiogenic factor acting directly on endothelial cells (Fig.…”
Section: Evaluation Of the Angiogenic Response Induced By Cxcl1/mip-2supporting
confidence: 66%
“…We have recently reported that the angiogenic activity of CXC-ELR ϩ chemokines in the Matrigel plug angiogenesis assay in vivo is neutrophil-dependent, as neutrophil depletion of the animals completely abrogated the angiogenic response to these agonists (10). In this study, we have identified a mechanism through which neutrophils exert this specific activity.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…47 Although expression of CXCR2 has also been reported in endothelial cells, 48,49 evidence has clearly shown that neutrophils are necessary mediators of the angiogenic response induced by CXCR2 agonists in vivo. 50 In wound-healing studies, angiogenesis begins immediately after injury and peaks after 7 days. 51,52 Our histologic analysis of tissue sections 72 hr after coinoculation of apoptotic cells and viable tumor cells showed a great number of newly formed blood vessels, which followed the appearance of MRP-14-positive leukocyte infiltrate in that area.…”
Section: Discussionmentioning
confidence: 99%
“…When delivered concurrently with angiostatin, IL-2 accumulated less in the spleen while more was found in the kidneys, the tumor, and systemically (Fig 3a, b). This may be related to angiostatin's ability to alter neutrophil trafficking 34 or adhesion molecule expression on endothelial cells. Angiostatin, when bound to integrins, 35 may alter trafficking of lymphocytes, while the expression of hypoxic-induced proangiogenic factors in tumors can alter the expression of cell adhesion molecules involved in systemic cell trafficking.…”
Section: Discussionmentioning
confidence: 99%